Lean Manufacturing dalam Reduksi Waste untuk Peningkatan Efisiensi Produksi Konektor Tipe X di PT XYZ - Muhammad Kyodan Khalidzky; Winarno; Wildan Fatchan Maulidin (Universitas Proklamasi 45, 2025)
Inefficient production processes can cause waste that results in delays, increased operational costs, and decreased productivity. Therefore, identifying and reducing waste is important in achieving better efficiency in the production process. This study aims to identify and reduce waste in the production process of type X connectors at PT XYZ by applying Lean Manufacturing principles. The methods used in this study include Value Stream Mapping (VSM) to map the production process flow and Process Activity Mapping (PAM) to analyze production activities in detail. The results of the analysis show that the largest waste occurs at the Operation stage (57.07%), followed by Transportation (26.65%) and Delays (10.89%). Based on the 5W + 1H analysis, it was found that the main causes of waste were the lack of measuring stations and inefficient warehouse layouts. Recommendations given include adding measuring stations, implementing IoT technology to automate data input, and optimizing warehouse layouts. The implementation of these improvements is expected to reduce waste, increase productivity, and help PT XYZ achieve production targets more efficiently.